2022
DOI: 10.1111/clr.13900
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐zygomatic infection associated with zygomatic implants: A retrospective longitudinal cohort study

Abstract: Objectives The main objective of this retrospective, longitudinal, cohort study was to describe the occurrence of peri‐zygomatic infection (PZI) as a complication associated with zygomatic implant (ZI) placement in a period of 22 years. Materials and methods A retrospective search was carried out in the department of oral and maxillofacial surgery of Saint John's hospital in Genk, Belgium. Patients that had a severely atrophic fully or partially edentulous maxilla, and at least one ZI placed, were included. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Figure 3 illustrates an overview of the number of implants placed and total complication events each year and Table 1 provides an overview of the ZI survival rate and its association with each complication. Amongst the infectious biological complications, sinusitis was the most commonly reported ( n = 138) occurring at a mean follow‐up time‐point of 4.5 years (range 0.04–19.37), followed by cheek soft tissue infection ( n = 72, 3.2 years, range 0.05–17.9), zygomatic region infection ( n = 39, 3.2 years, range 0.03–10.4), peri‐zygomatic infection ( n = 25, 1.9 years, range 0.01–10.4) (Vrielinck et al, 2022), oroantral communication ( n = 24, 5.3 years, range 0.1–19.4), gingival hyperplasia ( n = 24, 4.1 years, range 0.6–10.1), permanent intraoral dehiscence ( n = 16, 2.7 years, range 0.1–11.6), peri‐implantitis of the standard implant ( n = 11, 6 years, range 1.38–14.4), permanent oroantral communication ( n = 8, 2.2 years, range 0.4–3.9), orbital region infection ( n = 5, 3.4 years, range 1.7–5.6), and fracture of the zygomatic bone ( n = 2, 1.1 years, range 0.2–1.9).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3 illustrates an overview of the number of implants placed and total complication events each year and Table 1 provides an overview of the ZI survival rate and its association with each complication. Amongst the infectious biological complications, sinusitis was the most commonly reported ( n = 138) occurring at a mean follow‐up time‐point of 4.5 years (range 0.04–19.37), followed by cheek soft tissue infection ( n = 72, 3.2 years, range 0.05–17.9), zygomatic region infection ( n = 39, 3.2 years, range 0.03–10.4), peri‐zygomatic infection ( n = 25, 1.9 years, range 0.01–10.4) (Vrielinck et al, 2022), oroantral communication ( n = 24, 5.3 years, range 0.1–19.4), gingival hyperplasia ( n = 24, 4.1 years, range 0.6–10.1), permanent intraoral dehiscence ( n = 16, 2.7 years, range 0.1–11.6), peri‐implantitis of the standard implant ( n = 11, 6 years, range 1.38–14.4), permanent oroantral communication ( n = 8, 2.2 years, range 0.4–3.9), orbital region infection ( n = 5, 3.4 years, range 1.7–5.6), and fracture of the zygomatic bone ( n = 2, 1.1 years, range 0.2–1.9).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study found a positive association between zygomatic region infection and high torque force for achieving primary stability which could result in implant loss. Therefore, it is of vital importance that an equilibrium is achieved between sufficient primary stability and torque (Vrielinck et al, 2022). All these aforementioned factors are biological in nature with an infectious component which might get resolved following antibiotics administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Purulent processes of the zygomatic and perizygomatic area are not common. Among etiologies are: otitis media, 1,2 complication of zygomatic implants placement, 3,4 osteomyelitis, 5 medicationrelated osteonecrosis of the jaw (MRONJ), "Krokodil" drug-related osteonecrosis, 6 and odontogenic infection 7,8 . The last one in the peri-zygomatic area can manifest in a form of sinus tract 7 , abscess 8 , and even phlegmon 8 .…”
Section: Introductionmentioning
confidence: 99%
“…There is less surgical morbidity and is similar to a standard lateral sinus approach 8 . Potential complications compared to zygomatic implants are reduced as is surgical trauma to the patient during surgery and during the postoperative period 9 , 10 . The implant platform can be positioned at the mesial portion of the first molar or at the second premolar depending on the A-P spread required for proper posterior support.…”
mentioning
confidence: 99%